The Franconian Basin thermal anomaly, SE Germany revised: New thermal conductivity and uniformly corrected temperature data - Kämmlein, Marion; Bauer, Wolfgang; Stollhofen, Harald (Zeitschrift der Deutschen Gesellschaft für Geowissenschaften, 2020)
Exploration activities for hydrocarbons and thermal waters between the 1960s and 1980s consolidated the assumption of a positive temperature anomaly in the Franconian Basin of SE Germany. However, the geological causes of the temperature high are not known yet. In addition, an up-to-date compilation of temperature data from deep wells and thermal conductivity data of the Permo-Triassic section and of the basement rocks is lacking. In this study, we present a homogenised dataset of uniformly corrected temperature readings from 18 deep wells and new thermal conductivity data of the key strata of the Franconian Basin to constrain the geometry of the anomaly and to calculate reliable conductive surface heat flow densities. We further apply a vertical Péclet number analysis on equilibrated temperature logs for quantifying convective and conductive components in heat transfer. The isotherms of calculated equilibrium temperature gradients >30.0 - 48.9 °C km-1 constrain the presence of elevated temperatures in the Franconian Basin within an area of 100 x 65 km2. The elevated temperatures in the centre of the anomaly presumably originate in the basement but rapidly decrease away from the centre. The geothermal potential of the area is locally high, with surface heat flows exceeding 100 mW m-2 and reaching a maximum of 134(±16) mW m-2 in the central part of the anomaly. The NW-SE elongated shape of the anomaly implies that the strike of the major regional fault system has a significant control on the present-day temperature field. A Péclet number analysis and the correlation of T-log breaks with the new thermal conductivity data prove a predominantly conductive heat transfer regime. However, signatures of convective heat transfer have been proven for the aquifers of the Buntsandstein, Muschelkalk and Keuper groups. The study also reveals significant data gaps in the Franconian Basin, which strongly limit a reliable three-dimensional representation of the temperature field and a further limitation of possible cause(s) of the temperature anomaly. Namely, these are missing temperature data of the basement and a generally low density and the partially low depth level of available temperature dat
Keywords: temperature correction; temperature gradient; temperature anomaly; geothermal energy; heat flow density; Germany